2018
DOI: 10.1007/s11695-018-3246-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of GERD-Related Disorders in Obese Patients on PPI Therapy: a Population Analysis

Abstract: BackgroundIncreasing prevalence of obesity has shown an associated increase in gastroesophageal reflux disease (GERD)-related diseases. Proton pump inhibitor (PPI) therapy has been demonstrated to reduce the incidence of such diseases. The study’s aim was to analyze the Clinical Practice Research Datalink (CPRD) to determine factors that increase the propensity of obese patients on PPIs to develop Barrett’s esophagus (BE) and esophageal carcinoma.MethodA case-control population study was carried out, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, during PPI treatment, BMI was not a significant independent predictor of heartburn resolution or EE healing [26]. When obese patients are treated with PPI therapy for reflux, no increased risk of BE or oesophageal carcinoma has been observed [27]. If a GERD-induced cough is suspected in clinical practice, PPIs should be tested [6].…”
Section: Specificity Of the Clinical Approach Towards Chronic Cough I...mentioning
confidence: 99%
“…However, during PPI treatment, BMI was not a significant independent predictor of heartburn resolution or EE healing [26]. When obese patients are treated with PPI therapy for reflux, no increased risk of BE or oesophageal carcinoma has been observed [27]. If a GERD-induced cough is suspected in clinical practice, PPIs should be tested [6].…”
Section: Specificity Of the Clinical Approach Towards Chronic Cough I...mentioning
confidence: 99%
“…They were published between 1985 and 2022. Sixteen studies were performed in Asia, 19 34 16 in Europe, 35 50 14 in America, 51 64 and 1 in Oceania. 65 …”
Section: Resultsmentioning
confidence: 99%
“…In case of significant erosive esophagitis, PPI therapy is maintained even if it is asymptomatic (Badillo and Francis, 2014). Although, some recent studies demonstrated an increased risk of esophageal adeno carcinogenesis for patients taking PPIs especially for a long time (Cheung et al, 2018;Duan et al, 2009;Erridge et al, 2018;Kinoshita et al, 2018), not enough studies are performed on the side effects of long term consumption of PPIs on GERD in Iranian population.…”
Section: Gastro-esophageal Reflux Diseasementioning
confidence: 99%